Apgar score and neonatal mortality in a hospital located in the southern area of São Paulo city, Brazil - Tatiana Gandolfi de Oliveira; Paula Vieira Freire; Flávia Thomé Moreira; Juliana da Silva Bemfeito de Moraes; Raquel Coris Arrelaro; Sarah Rossi; Viviane Alves Ricardi; Yara Juliano; Neil Ferreira Novo; José Ricardo Dias Bertagnon (Einstein (São Paulo), 2012)
OBJECTIVE: To correlate the Apgar score, and neonatal mortality and its causes at a hospital located in the southern area of São Paulo City. METHODS: A retrospective study performed by analysis of medical charts (n=7,094) of all live newborns during the period of 2005 to 2009, with data up to 28 days of life in reference to weight, Apgar score, survival and cause of mortality. Cases were analyzed by the X² test (p < 0.05). RESULTS: In 7,094 births, there were 139 deaths, 58.3% during the first week, and 3.6% of them with Apgar < 4 in the 1st minute. A positive association was found between mortality and this variable, with significantly declining values up to 2,000 g in weight. In the group with weight < 1,000 g, the association with Apgar < 4 in the 1st minute with mortality was three-fold greater than in the 1,000-1,500 g weight group, and 35-fold greater than in the > 3,000 g group. Among newborns with Apgar 8-10, the rate of mortality and low weight was two times greater than in those with weight > 2,499 g. Fetal distress and prematurity were associated with early neonatal death; malformations and fetal distress to late mortality. The predictive value of death with Apgar < 4 varied, according to weight, from 62.74% in the < 1,000 g group to 5.5%, in the > 3,000 g group. CONCLUSIONS: The Apgar score proved linked to factors both epidemiological and related to attention given to the birth and neonatal mortality, and was associated with extremely low birth weight.